IMF Survey, Volume 35, Issue 21. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
John Lipsky's visit to South Africa and Mali, Latin American growth, Uruguay repays loan, Eastern Europe, Albania's economy, Belarus and Morocco, U.S. current account deficit, Francis Warnock, IMF governance, fiscal adjustment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet